The Role of the Process Organizational Structure in the Development of Intrapreneurship in Large Companies - Adisa Delić; Sabina Đonlagić Alibegović (Naše gospodarstvo/Our economy, 2016)
Modern companies’ business environments have become increasingly complex, dynamic, and uncertain as a consequence of globalization and the rapid development of information communications technology. Companies are urged to increase their flexibility in order to keep their competitiveness in the global market. The affirmation of intrapreneurship becomes one of the basic ways for achieving higher adaptability and competitiveness of large companies in the modern business environment. In this context, the choice of an organizational solution that improves the development of entrepreneurial orientation and increases employee entrepreneurship and innovativeness becomes an important task for large companies. Research studies and business practices have indicated that various types of modern organizational forms enable the development of intrapreneurship. Therefore, the main aim of this paper is to identify dominant characteristics of organizational solutions and analyse their influence on the development of intrapreneurship in large companies in Bosnia and Herzegovina (BiH). The research results indicate that current organizational characteristics are not favourable for the development of intrapreneurship in large BiH companies and that improvement is necessary in order to create an enabling environment for intrapreneurship and innovativeness. Based on these findings, recommendations for appropriate organizational changes are presented that might result in a more intensive development of intrapreneurship in large BiH companies.